Direct‐acting antiviral treatment of chronic HCV‐infected patients on opioid substitution therapy: Still a concern in clinical practice?. (23rd January 2018) - Christensen, Stefan; Buggisch, Peter; Mauss, Stefan; Böker, Klaus H. W.; Schott, Eckart; Klinker, Hartwig; Zimmermann, Tim; Weber, Bernd; Reimer, Jens; Serfert, Yvonne; Wedemeyer, Heiner
Abstract: Background and aims: There is limited real‐world information on the effectiveness of antiviral treatment of chronic hepatitis C virus (HCV) infection with direct‐acting antivirals (DAA) in people on opioid substitution therapy (OST). This study compared sustained virological response (SVR) rates and proportion of lost to follow‐up (LTFU) between OST and non‐OST patients in the German Hepatitis C‐Registry (DHC‐R). Design: National multi‐centre prospective real‐world registry (German Hepatitis C‐Registry, DHC‐R). Non‐OST patients comprised patients with former/current drug use (non‐OST/DU) and patients never consuming drugs (non‐OST/NDU). Setting: A total of 254 medical centres in Germany, including 123 centres providing OST. Participants: A total of 7747 chronic HCV patients started DAA therapy (739 OST and 7008 non‐OST; 1500 non‐OST/DU; 5508 non‐OST/NDU) patients. Five hundred and twenty‐eight OST and 5582 non‐OST patients had completed antiviral therapy and at least one follow‐up documentation [intention‐to‐treat (ITT) population]. Measurements: Study outcomes were SVR, proportion of LTFU and safety of treatment. Findings: SVR (ITT) was documented in 85% (450 of 528) OST patients versus 86% (969 of 1126) in non‐OST/DU ( P  = 0.651) and 92% (4113 of 4456) non‐OST/NDU ( P  < 0.001) patients. Independent predictors for SVR ( P  < 0.01 in multivariate analysis) included HCV genotype non‐3 [adjusted odds ratio (aOR) = 1.11; 95% confidence interval (CI) = 1.07–1.15], female sex (aOR = 1.59; CI = 1.30–1.94), platelet counts >90 × 109/l (aOR = 1.51, CI = 1.14–2.01), cirrhosis (aOR = 0.77; CI = 0.62–0.96) and patient group (OST/DI (aOR = 0.58; CI = 0.42–0.78); non‐OST/DU (OR: 0.63; CI = 0.50–0.78). In per‐protocol analysis (PP), SVR rates were ≥ 94% in all patient groups. In OST the proportion of LTFU was higher (10.2%) than in non‐OST/DU (8.5%) and non‐OST/NDU (3.2%, P  < 0.001) patients. Independent factors for LTFU ( P  < 0.01) were HCV genotype non‐3 (aOR = 0.92; CI = 0.88–0.96), female sex (aOR: 0.7; CI = 0.53–0.92), pre‐treatment (aOR = 0.64; CI = 0.50–0.82), OST/DI (aOR = 3.35; CI = 2.35–4.78) and non‐OST/DU (aOR = 2.38; CI = 1.80–3.14). Conclusions: In Germany, direct‐acting antiviral treatment of former or current drug users with or without opioid substitution therapy can achieve equally high sustained virological response rates as in patients with no history of drug use.